2020
DOI: 10.1158/1538-7445.am2020-ct011
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT011: Evaluation of durvalumab in combination with olaparib and paclitaxel in high-risk HER2 negative stage II/III breast cancer: Results from the I-SPY 2 TRIAL

Abstract: Background: I-SPY2 is a multicenter, phase 2 trial using response-adaptive randomization within molecular subtypes defined by receptor status and MammaPrint risk to evaluate novel agents as neoadjuvant therapy for breast cancer. The primary endpoint is pathologic complete response (pCR, ypT0/is ypN0)). DNA repair deficiency in cancer cells can lead to immunogenic neoantigens, activation of the STING pathway, and PARP inhibition can also upregulate PD-L1 expression. Based on these rationales we tested the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The GeparNuevo trial in TNBC demonstrated a numerical but not statistically significant increase in pCR rate (53% vs. 44%, p = 0.287) when durvalumab (1500 mg every 4 weeks) was included with weekly nab-paclitaxel (125 mg/ m 2 ) and epirubicin/cyclophosphamide 16 . The Bayesian randomized I-SPY2 trial evaluated the combination of 1500 mg durvalumab every 4 weeks and olaparib 100 mg twice a day concurrent with weekly paclitaxel (80 mg/kg) followed by AC without durvalumab or olaparib vs. the same chemotherapy regimen alone and reported an increase in pCR rate from 27 to 47% in the TNBC population of the trial with a 98% probability that the experimental arm is superior to the control 17 . The 95% confidence interval of the pCR point estimate in our trial includes the pCR rates seen in the immunotherapy arms of both these randomized trials and therefore the results are consistent with an improvement in pCR rate with the inclusion of durvalumab.…”
Section: Discussionmentioning
confidence: 99%
“…The GeparNuevo trial in TNBC demonstrated a numerical but not statistically significant increase in pCR rate (53% vs. 44%, p = 0.287) when durvalumab (1500 mg every 4 weeks) was included with weekly nab-paclitaxel (125 mg/ m 2 ) and epirubicin/cyclophosphamide 16 . The Bayesian randomized I-SPY2 trial evaluated the combination of 1500 mg durvalumab every 4 weeks and olaparib 100 mg twice a day concurrent with weekly paclitaxel (80 mg/kg) followed by AC without durvalumab or olaparib vs. the same chemotherapy regimen alone and reported an increase in pCR rate from 27 to 47% in the TNBC population of the trial with a 98% probability that the experimental arm is superior to the control 17 . The 95% confidence interval of the pCR point estimate in our trial includes the pCR rates seen in the immunotherapy arms of both these randomized trials and therefore the results are consistent with an improvement in pCR rate with the inclusion of durvalumab.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting a role for immune checkpoint neoadjuvant therapy in high-risk ER-positive/HER2-negative breast cancer was the graduation of the PD-L1 inhibitor antibody durvalumab and the PARP inhibitor olaparib in combination with paclitaxel in the ER-positive/HER2-negative signature, driven by the MammaPrint ultrahigh (MP2) subgroup. In the MP2 subgroup, durvalumab/olaparib/paclitaxel combination exhibited a pCR of 64% versus 22% for the control chemotherapy arm 50 .…”
Section: Rationale For Nac For High-risk Er-positive/her2-negative Brmentioning
confidence: 94%
“…Indeed, pembrolizumab was the first agent of the initial nine tested that showed an improvement of pCR rates in the ER-positive/HER2-negative signature. This result was recently followed by the graduation of the PD-L1 antibody durvalumab in combination with olaparib and paclitaxel in the MammaPrint ultrahigh (MP2) ER-positive/HER2-negative signature, where a pCR rate of 64% was observed relative to 22% for control 50 . In TNBC, targeting the PD-1/PD-L1 checkpoint with pembrolizumab increased pCR rates from 22 to 60% 44 and with durvalumab/olaparib/paclitaxel from 27 to 47% 50 .…”
Section: Highlights and Future Directionsmentioning
confidence: 97%
See 2 more Smart Citations